Summary of European Advanced Accelerator Workshop (EAAC) Working Group 1: Electron Beams from Plasma. (July 2020) - Corde, Sebastien; Irman, Arie; Turner, Marlene
Abstract: We summarize oral contributions presented in Working Group (WG) 1 of the European Advanced Accelerator Workshop (EAAC). Working Group 1 is titled 'Electron Beams from Plasma' and included presentations and discussions on the following subjects: laser- and beam-driven plasma wakefield acceleration, recent experimental results and planned experiments, single and multi drive laser pulses (or particle bunches), external and self-injection techniques, staging as well as advanced beam control and manipulation.